Determination of Pancreatic Beta Cell Reserve in Antidepressant Users and Evaluation of Its Relationship with Metabolic Parameters: A Cross-Sectional Study - Kaya, Kamer; Gürok, Mehmet Gürkan; Kilinc, Faruk; Ustundag, Bilal; Örüm, Mehmet Hamdi; Atmaca, Murad (My University, 2024)
Objective: The aim of this study was to determine the pancreatic ?-cell reserve by means of homeostatic model assessment for insulin resistance (HOMA-IR) in patients followed up with the diagnoses of major depressive disorder and anxiety disorder and being treated with antidepressants, and to investigate the relationship between the pancreatic ?-cell reserve and various metabolic markers. Materials and Methods: The fasting blood glucose and insulin levels and various biochemical parameters of 60 patients using antidepressants and 60 healthy control subjects were measured and their HOMA-IR values were calculated. Results: Both the patient and control groups consisted of 32 (53.3%) females and 28 (46.7%) males. There was no significant difference between the groups in terms of age (p=0.275). The median duration of antidepressant use of the patients was 27 (min:12, max:48) months. Weight, body mass index and waist, hip and neck circumferences of the patient group were significantly higher than those of the control group (p<0.05). The insulin, C-peptide and HOMA-IR values of the patient group were also significantly higher than those of the control group (p<0.05). There was no significant difference between the patient and control groups in terms of fasting blood glucose and hemoglobin A1c (HbA1c) values (p>0.05). On the other hand, total cholesterol and low-density lipoprotein (LDL) values of the patient group were found to be significantly higher than those of the control group (p<0.05). Conclusion: The findings of this study indicated that the use of antidepressants is associated with an increase in C-peptide and HOMA-IR levels, which are positively correlated with insulin resistance.
Keywords: Insülin; HOMA-IR; Antidepressant; beta cell reserve